PELATIHAN BAHASA JEPANG DASAR BAGI ANAK-ANAK TUKANG SUWUN DI PASAR BADUNG - I G OEINADA; N M WIRIANI; NLK YULIANI GIRI; NM ANDRY ANITA DEWI; SILVIA DAMAYANTI; K WIDYA PURNAWATI (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2015)
This community service was intended to introduce Japanese language and culture to children who haveprofession as labor at Pasar Badung in Bali. Although they are in school-age, because of economic and otherreasons, they have to give priority to economics activities rather than their own education. This communityservice was held by the staff and students of Japanese Department, Udayana University’s on Friday, August 01st,08th, and 15th, 2014. The location is at Sanggar Belajar Anak Pasar Badung, 4th floor Pasar badung. The methodsused in training Japanese language and culture to them were orientation, drills, and feedback. There were a lotof benefits obtained by the children from this community service activit, they can learn about basic Japaneselanguage as well as Japanese culture via animated cartoons played during lunch breaktime. To the students asthe assistant-instructors of this activity, can learn about real situation language teaching process and handlequestions and overcome difficulties in the process. To the lecturers as the advisers of this activity, they can devotetheir knowledge as an implementation of Tri Dharma Perguruan Tinggi.